Meningkatkan Kreativitas Anak melalui Media Bahan Bekas - Cicik Setyowati (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The world of children is play and learning that engages all five senses. Playing is synonymous with activities that are fun, exhilarating, and filled with a joyful and cheerful atmosphere. Playing that is done by children requires supporting tools and materials. One of the learning support facilities is with children's learning resources in kindergarten, RA and KB. The source of learning for kindergarten, Ra and KB children is the use of educational educational tools or better known as APE. Learning tools or media can be made yourself with materials that are easy to find without having to always buy and using these used materials can help reduce ecosystem pollution on the soil. Utilization of waste will be maximized if managed and innovated according to its type and use. This study used a Classroom Action Research method consistingof Cycle I and Cycle II. It can be concluded, one of the ways to increase children's creativity is by using used goods. Evidenced by the increase in student outcomes. The results in the first cycle showed